2015
DOI: 10.4103/0019-509x.176727
|View full text |Cite
|
Sign up to set email alerts
|

Solid pseudopapillary tumor of the pancreas: A retrospective analysis of 36 cases from a single institution in India

Abstract: This study suggests that a management approach with only limited complete tumor resection would be adequate in these tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…In the present study, SPEN was found to be the most commonly occurring PCN. This was in conformance with three other prior studies, one of which is from the author's institution (7,15,16) (Table 5). This could either mean increased surgical resections for SPEN due to symptomatic presentation and large size as found in our study, or might indicate a true increase in the prevalence of SPEN.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, SPEN was found to be the most commonly occurring PCN. This was in conformance with three other prior studies, one of which is from the author's institution (7,15,16) (Table 5). This could either mean increased surgical resections for SPEN due to symptomatic presentation and large size as found in our study, or might indicate a true increase in the prevalence of SPEN.…”
Section: Discussionsupporting
confidence: 91%
“…SPTP which is an extremely rare tumor, typically affects women in their second or third decade of life. However, a small number of male patients with SPTP have also been reported in the literature [5][6][7] . In a large series, female to male ratio was reported to be 16/3 8 .…”
Section: Epidemiologymentioning
confidence: 99%
“…stated that complete surgical removal of even recurrent tumors is the best option and reported that SPTP recurrence did not adversely affect overall survival in their pediatric series 5,6 . Some researchers suggest that a treatment approach that includes only limited tumor resection such as enucleation, with negative surgical margins will be sufficient for these tumors 7,8 . The optimal surgical strategy for SPNP in children remains controversial.…”
Section: Introductionmentioning
confidence: 99%